Differential response from selection for low birth weight versus high calving ease in beef cattle - Saad, Hamad M. A., author; Enns, Mark, advisor; Thomas, Milton, advisor; Peel, Kraig, committee member; Frasier, Marshall, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Keywords: American Simmental beef cattle; birth weight; calving ease; model comparison; selection; threshold model